2018
DOI: 10.1080/13657305.2018.1510997
|View full text |Cite
|
Sign up to set email alerts
|

Price interactions between wild and farmed products: Turkish sea bass and sea bream markets

Abstract: We investigate empirically market interactions in the Turkish wild and farmed sea bass and sea bream markets. For gilthead sea bream and European sea bass, we conduct a Granger causality test between the prices of the wild and farmed products, based on the estimation of a vector autoregressive model. Our data set consists of annual fish prices from 1996 to 2016. Our empirical results show that the wild and farmed sea bass are neither substitutes nor complements : the markets for each product are independent. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The production of farmed seabream and seabass was 376,984 tonnes valued at 2,066 million USD in 2016 2 . The capture sector is relatively unimportant for these species as it represented less than 4% of total volumes, and the catches are mostly found to compete in a separate market (Bjørndal and Guillen, 2017;Regnier and Bayramoglu, 2017;Bayramoglu, 2019). About 95% of the production is located in the Mediterranean.…”
Section: Overview Of the Seabream And Seabass Industry And Marketsmentioning
confidence: 99%
“…The production of farmed seabream and seabass was 376,984 tonnes valued at 2,066 million USD in 2016 2 . The capture sector is relatively unimportant for these species as it represented less than 4% of total volumes, and the catches are mostly found to compete in a separate market (Bjørndal and Guillen, 2017;Regnier and Bayramoglu, 2017;Bayramoglu, 2019). About 95% of the production is located in the Mediterranean.…”
Section: Overview Of the Seabream And Seabass Industry And Marketsmentioning
confidence: 99%
“…Despite competition at seabream markets in the Mediterranean has increased significantly in recent decades, the literature that helps to understand the competitive relations across this value chain is scarce. Most of the studies focused in competition between wild and farmed seabream, and found that they form two differentiated products in the Spanish market (Rodriguez et al 2013;Regnier and Bayramoglu, 2017;Bjørndal and Guillen, 2017a,b;Bayramoglu, 2019). However, few studies have focused on analyzing market integration between different geographic areas (Bjørndal et al 2019) and price interactions along the value chain.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have mostly focused on salmon in the EU and US (Gordon, Salvanes, & Atkins, 1993;Mickwitz, 1996;Jaffry, Pascoe, Taylor, & Zabala, 2000;Asche, 2001;Setälä et al, 2003;Virtanen, Setälä, Saarni, & Honkanen, 2005), shrimps in the EU and US (Béné, Cadren, & Lantz, 2000;Kennedy & Lee, 2005;Asche, Bennear, Oglend, & Smith, 2012;Ankamah-Yeboah, Ståhl, & Nielsen, 2017;Ankamah-Yeboah & Bronnman, 2018), and catfish/tilapia in the US (Ligeon, Jolly, & Jackson, 1996;Quagrainie & Engle, 2002;Kennedy & Lee, 2005;Hong & Duc, 2009;Norman-López & Bjørndal, 2009). In 3 Studies show that farmed European seabass does not compete with wild seabass species in France (Regnier and Schubert, 2016;Regnier and Bayramoglu, 2017), Italy (Brigante and Lem, 2001), Spain (Rodriguez Rodriguez and Bande Ramudo, 2015;Bjørndal and Guillen, 2017a) and Turkey (Bayramoglu, 2018). many cases, substitutability between farmed imports and domestic produce is confirmed, even if there are some exceptions (see for a review Bjørndal and Guillen, 2016).…”
Section: Introductionmentioning
confidence: 99%